Peran Guru Pendidikan Agama Islam dalam Membentuk Sikap Sopan Santun Peserta Didik - Erik Wiranata; Prihantoro (Najah Bestari, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in shaping polite behavior among eleventh-grade students at SMAN 2 Rejang Lebong, as well as to identify the strategies employed, supporting factors, and inhibiting factors in its implementation. This research adopts a descriptive qualitative approach. The study was conducted at SMAN 2 Rejang Lebong from November to December 2025. Data were collected through observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing.The findings indicate that PAI teachers play a very important role in shaping students’ polite behavior through role modeling, habituation of polite conduct, moral guidance, and the integration of politeness values into Islamic Religious Education learning. The strategies applied by PAI teachers include the habituation of polite attitudes, the provision of advice, and an educative and humanistic approach in learning interactions. Supporting factors in the formation of polite behavior include a religious school culture, support from school policies, and collaboration among teachers. Meanwhile, inhibiting factors include the influence of the external environment, social media, and differences in students’ family backgrounds. This study concludes that the formation of students’ polite behavior requires the consistent and sustainable role of PAI teachers as well as synergistic support from schools, families, and the wider community.